Supplementation of grass hay with molasses in crossbred (Bos taurus X Bos indicus) non-lactating cows: effect of level of molasses on feed intake, digestion, rumen fermentation, and rumen digesta pool size - Khalili, H. (1993)
The paper evaluates the effects of the level of sugar cane molasses on feed intake, diet digestibility, DM degradation of grass hay, rumen pool sizes and rumen fermentation. Five ruminally fistulated crossbred cows were given a basal diet of grass hay ad libitum and cottonseed cake. The other four diets were supplemented with molasses or sodium bicarbonate. The voluntary intake of hay decreased with the level of molasses. The apparent digestibility of total DM increased but of NDF decreased the effect of molasses diets. Sodium bicarbonate did not affect the intake of hay or the digestibilities of different dietary constituents The disappearance of hay DM from nylon bags decreased with the level of molasses. The rumen pool sizes of total ingesta and DM were smaller with molasses diets. The rumen pool size of NDF was not affected by the treatment. Molasses decreased the mean value of rumen PH and concentration of ammonia N. The molar proportions of acetate decreased and propionate and butyrate increased with the level of molasses. Sodium bicarbonate did not change the fermentation pattern.